Influence of personality traits on online self-disclosure: Considering perceived value and degree of authenticity separately as mediator and moderator - Lv, Yuxiang; Fang, Gege; Zhang, Xiaoxue; Wang, Yafei; Wang, Yihuan (Frontiers in Psychology, 2022)
The Chinese have been spending significantly more time on the internet in post-pandemic time. When people are confined indoors, there is a greater need to construct an identity and socialize online. Personality traits and perceived value of the media are important factors that affect users’ online self-disclosure. This study involved the construction of a mediation model and a moderator model to evaluate the influence of personality traits on self-disclosure on social media. Perceived value was regarded as the mediator while the degree of authenticity was regarded as the moderator. Using a quota sampling method, 1,075 Chinese netizens were surveyed in July and August 2021. The results showed that: 1. The depth of self-disclosure of subjects with extroverted personality was significantly higher than that of those with introverted personality, that is, personality traits affect the depth of self-disclosure; 2. perceived value plays a mediating role in online self-disclosure; 3. The degree of authenticity is a significant moderator in the relationship between personality and self-disclosure. In all, the results from this study contribute to our understanding of how personality traits affect perceived value of media and self-disclosure. This study tested the credibility and validity of the proposed model in the context of the recent COVID-19 pandemic lockdown in China, and the study is a novel approach in that area of research.